Preparation and Characterization of Green Fe3 O4 Nanoparticle Using the Aqueous Plant Extract of Gundelia tournefortii L. - Jalal, Aveen F.; Fakhre, Nabil A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
In this work, the magnetite nanoparticles (Fe3O4-NPs) synthesized using a simple, fast, and environmentally acceptable green approach. Gundelia Tournefortii Extract, an aqueous plant extract, was used for the first time in green synthesis to prepare nanoparticles as reducing, capping, and stabilizing agents. Such biomolecules as flavonoids, alkaloids, and antioxidants are found in the aqueous leaf extract, and their presence has been determined to have an important role in the synthesis of Fe3O4-NPs. The techniques used in this analysis include Fourier Transform Infrared, Scanning Electron Microscopy, Energy-Dispersive X-ray spectroscopy, X-ray Diffraction, Transmission Electron Microscopy, and Vibrating Sample Magnetometer. The Vibrating Sample Magnetometer demonstrated that the samples were superparamagnetic, with a magnetization value of 48.6 emu/g. The prepared nanoparticle was applied to remove Chrystal Violet (CV), Malachite Green(MG), and Safranin (S) dyes from prepared aqueous solutions with the adsorption capacity of 13.9, 15.6, and 14.4 mg/g respectively.